Factors influencing the development and implementation of e-Government services in China - Yang, Zongpu; Ku Samsu, Ku Hasnita (Human Resource Management Academic Research Society, 2023)
Information and communication technology (ICT) rapidly transforms global government service delivery through modernized infrastructure. As an economic giant, China recognizes the need to centralize operations and enhance service delivery through e-government services. While e-government services have gained significant momentum globally, the specific factors that influence the development and implementation of these services in the Chinese context need to be explored. Therefore, this research investigates the factors driving the development and implementation of e-government services in China. Quantitative methods were employed, involving 200 participants actively engaged in e-government initiatives. A purposive sampling technique was used during the data collection to specifically get the responses from targeted relevant government officials and users. Descriptive statistics analysis was employed to analyze collected data. Variables such as trust in e-government, policy coherence, service effectiveness, and user satisfaction were measured. The findings of this study reveal that trust, policy coherence, service effectiveness, and user satisfaction are key factors influencing the development and adoption of e-government services in China. This research provides insights into China's efforts to establish a digital government and contributes to the global understanding of e-government development.